2014
DOI: 10.1080/08964289.2014.897931
|View full text |Cite
|
Sign up to set email alerts
|

Bradycardia as a Marker of Chronic Cocaine Use: A Novel Cardiovascular Finding

Abstract: Background Few studies have examined the effects of chronic cocaine use on the resting surface electrocardiogram (ECG) between exposures to cocaine. Methods 12-lead ECGs from 97 treatment-seeking cocaine-dependent subjects were compared to ECG parameters from 8513 non-cocaine-using control subjects from the Atherosclerosis Risk in Communities study. Results After matching and adjusting for relevant covariates, cocaine use demonstrated large and statistically reliable effects on early repolarization, bradyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…For example, in a recent study utilizing coronary computed tomography angiography, Ebersberger et al [47] demonstrated more pronounced coronary atherosclerosis in cocaine users experiencing acute chest pain, even in the absence of an acute coronary event, compared to non-cocaine users. Others have reported signs of cardiovascular damage, including increased systolic blood pressure, aortic stiffness, increased left ventricular mass, and bradycardia, in otherwise healthy young individuals who chronically use cocaine [32][33][34]. This chronic cardiovascular damage results in an increased risk of the acute coronary syndromes described above as well as risks for diseases associated with ongoing myocardial cell death and atherosclerotic processes, such as cardiomyopathy [48][49][50][51] and endocarditis.…”
Section: Long-term Cardiovascular Consequencesmentioning
confidence: 88%
See 1 more Smart Citation
“…For example, in a recent study utilizing coronary computed tomography angiography, Ebersberger et al [47] demonstrated more pronounced coronary atherosclerosis in cocaine users experiencing acute chest pain, even in the absence of an acute coronary event, compared to non-cocaine users. Others have reported signs of cardiovascular damage, including increased systolic blood pressure, aortic stiffness, increased left ventricular mass, and bradycardia, in otherwise healthy young individuals who chronically use cocaine [32][33][34]. This chronic cardiovascular damage results in an increased risk of the acute coronary syndromes described above as well as risks for diseases associated with ongoing myocardial cell death and atherosclerotic processes, such as cardiomyopathy [48][49][50][51] and endocarditis.…”
Section: Long-term Cardiovascular Consequencesmentioning
confidence: 88%
“…Over time, with ongoing cocaine use hypertension, aortic stiffness, left ventricular mass, and other measures of adverse cardiovascular dynamics progressively worsen in otherwise healthy young individuals [32][33][34]. In combination, these effects can result in myocardial ischemia, infarction, and other long-term deleterious effects.…”
Section: Imaging Evidencementioning
confidence: 95%
“…Recent reports have demonstrated that chronic cocaine use is a strong predictor of sinus bradycardia compared with a matched group of nonusers and resulted in three-to sevenfold increased risk of sinus bradycardia [5][6][7]. Despite the presence of sinus bradycardia, all patients were able to augment their sinus rate with activity [6].…”
Section: Sinus Bradycardia and Early Repolarization Patternmentioning
confidence: 86%
“…Sharma et al have showed also that current cocaine dependence corresponds to an increased odd of demonstrating early repolarization by a factor of 4.92 [5].…”
Section: Sinus Bradycardia and Early Repolarization Patternmentioning
confidence: 99%
See 1 more Smart Citation